Immune Cells Act as Promising Targets for the Treatment of Bone Metastasis - Luo, Guojing; He, Yuedong; Zhao, Qian; Yu, Xijie (Recent Patents on Anti-Cancer Drug Discovery, 2017)
Background: Bone metastasis is a common complication of certain types of cancer, and unfortunately, it is still incurable to date. Immune system is a major defence against tumor cells and bone metastasis. However, the immunodeficient mouse models are widely used in most researches of bone metastasis, thereby excluding the regulatory roles of the immune system in bone metastasis. Objective: The aim was to provide a comprehensive overview on the cellular and molecular mechanisms by which immune cells interact with tumor cells and bone cells, as well as recent related patents. Method: We performed a literature search of PubMed database for the current knowledge on the interaction between bone metastasis and immune system. Recent related patents were obtained from World Intellectual Property Organization (WIPO) website. Results: Immune cells in the bone-tumor microenvironment include dentritic cells, monocytes/ macrophages, myeloid-derived suppressor cells, regulatory T cells, T helper cells, neutrophil, CD4+ T lymphocytes, CD8+cytotoxic T lymphocytes, and natural killer cells, et al. In addition to their well-known immunomodulatory function, recent studies revealed that immune cells could cooperate with tumor cells and bone cells to enhance bone metastasis and tumor progression. There are some patents targeting immune system to inhibit bone metastasis. Conclusion: Immune cells are instigated by tumor cells to enhance the occurrence and the development of bone metastasis. Taking full advantage of anti-tumor roles of immune cells may bring the promise of a possible cure for bone metastasis.
Keywords: Bone metastasis